Celebrations - Craven, Jerry (Vero Beach, Fla. : Rourke Publications, 1996)
Details the rituals and celebrations that mark special days in a person's life, including birthdays, name days, the bar mitzvah, and marriage.
Includes index.
6.0
3-6
Keywords: Holidays -- Juvenile literature; Birthdays -- Juvenile literature; Special days -- Juvenile literature; Birthdays; Holidays; Birthdays; Holidays; Birthdays; Holidays